Hubungan Status Gizi Dengan Kejadian Diare Pada Balita Usia 24-59 Bulan di Wilayah Kerja Puskesmas Setu 1 - Yossi Tiasafitir; Mally Ghinan Sholih; Lely Sulfiani (Peneliti.net, 2022)
Lack of or poor nutrition in children will cause a decrease in the immune response, which means the ability to defend themselves against infection will decrease. One of the infectious diseases that still often occurs in toddlers is diarrhea. This type of research is an observational study with a cross sectional design which aims to determine whether there is a relationship between nutritional status and the incidence of diarrhea at the Setu Health Center 1. The number of samples studied was 100 respondents using purposive sampling technique. Data were obtained from the results of distributing questionnaires. The data from this study were processed by the chi square statistical test. Based on the chi square statistical test, it was found that the value of p = 0.080 which indicates that there is no relationship between nutritional status and the incidence of diarrhea in children under five in the working area of the Puskesmas Setu 1. The value of the prevalence ratio is 0.6, which means that nutritional status is the status of a protective factor. occurrence of diarrhea. From the results of the data analysis, it can be concluded that there is no relationship between nutritional status and the incidence of diarrhea in children under five at the Puskesmas Setu 1.